Identifikasi Spesies Meloidogyne spp. Penyebab Umbi Bercabang pada Tanaman Wortel di Jawa Timur - Zalzilatul Hikmia Hikmia; Supramana .; Gede Suastika (Jurnal Fitopatologi Indonesia, 2012)
Branched tuber is a new disease in carrot cultivation in Indonesia and has caused big losses for farmers. In 2010, several species of root-knot nematodes, Meloidogyne spp., were reported as the primary cause of disease and the yield loss due to the disease in the region of Agropolitan-Cianjur, West Java, reached 15% to 95%. Symptoms of tuber branching has also been reported in one of the centers of vegetable production in East Java, in the subdistrict of Bumiaji, Kota Batu. Research aimed at identifying  Meloidogyne species on carrot was carried out on carrot plantation. The study consisted of two activities, i.e. surveillance and identification. Surveillance was carried out at three different altitudes/elevations, i.e. 1600 m, 1700 m and 1800 m asl (above sea level). Identification was done by PCR ITS r-DNA using multiplex primer for mix spesies identification of M. hapla, M. fallax, and M. chitwoodi and the spesific primer for identification of M. arenaria, M. incognita, and M. javanica. Identification based on ITS r-NA by PCR gave positive results for four species, namely M. hapla, M. arenaria, M. incognita, and M. javanica.Key words: branched tuber disease, carrot, Meloidogyne, PCR ITS r-DNA